FUNGSI PENGAWASAN DPRD DALAM MEWUJUDKAN PELAKSANAAN PEMERINTAHAN DAERAH YANG BAIK - H. Achmad Fauzi (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
The new paradigma in the Law No. 32 Year 2004 on Regional Goverment still wants an equal relationship between the Local Government Council. The parallel relationship indicates that the position of Parliament and Locl Government is equality strong position. It was necessary in order to realize good governance (good governance), which is offset by an effective monitoring system and efficient through the mechanism of checks and balance. Good Governance ( Good Government ) is a government run by the norms or laws that govern them consistenly and responsibly in order to achieve the goal state that is based on the principle of transparent, accountable clean, honest and trustworthy. To realize good local governance, then the function Legislative Council in the exercise supervision over the implementation of the Local Government affairs is very important. Parliament's oversight includes decisions that are common outside of legislation such as the head of regional policy. Parliament as a body area legeslatif implement legislative function, budget and oversight. In conjunction with the oversight function, Parliement to supervise the implementation of the Local Government Supervision is essentially an act of judge / lest if something has been going according attempted repairs, the most important not to mistake happen again. Thus, it can be understood that the function of Parliament is an activity monitoring to assess the performance of duties as a de facto government within the framework of the creation of good local governance.